Pengaruh Kompetisi Politik dan Kekuatan Politik terhadap Transparansi Pengelolaan Keuangan Daerah - Fadila Sri Mulyati; Deviani Deviani (Universitas Negeri Padang, 2023)
This study aims to determine the effect of political competition and political strength on the transparency of district/city regional financial management on the island of Sumatra. This type of research is quantitative research, the type of data using secondary data. The population in this study were 154 districts/cities on the island of Sumatra with a total sample of 125 samples for one year of observation namely 2021. The data analysis technique used in this study was multiple regression analysis. The results of this study are that political strength has a significant negative effect on the transparency of regional/cities on the island of Sumatra in 2021. However, the political competition variable has no effect on the transparency of regional financial management in districts/cities on the island of Sumatra in 2021.